Clinical study of microbiological organisms causing liver abscess - Suraj, Lisha; Kadam, Pallavi S. (International Surgery Journal, 2021)
Background: Liver abscess is a disease reported commonly in developing countries like India. It can be amoebic or pyogenic liver abscesses, the diagnosis of which is challenging to treating physicians. This clinical study was con-ducted to identify the common microbiological organisms causing liver abscess so that proper treatment can be administered. Methods: A prospective study was conducted in MGM Medical College and Hospital, Navi Mumbai for a period of 2 years in 50 patients diagnosed with liver abscess. Pus culture and blood culture were carried out in all patients and data recorded and analyzed for microbiological profile. Results: The pus and blood cultures were showing growth in 90% of the liver abscess patients. Klebseilla was the most common organism identified in liver abscess followed by Staphylococcus aureus. Conclusions: Most of the patients had polymicrobial organisms identified in the aspirate of which 29% were Klebseilla pneumoniae, the commonest organism.